UV-visible spectrophotometry of waters and soils - Burgess, Christopher; Thomas, Olivier (Amsterdam, Netherlands Elsevier, 2023)
"UV-Visible Spectrophotometry of Waters and Soils, Third Edition presents the latest information on the use of UV spectrophotometry for environmental quality monitoring. Using practical examples, the book illustrates how this technique can be a source of new methods of characterization and measurement. Easy and fast to run, this simple and robust analytical technique is one of the best ways to obtain a quantitative estimation of specific or aggregate parameters (e.g., Nitrate, TOC) and simultaneously qualitative information on the global composition of waters and soils. This third edition presents current methods and applications for water quality monitoring, including recent works and developments. Writing from years of experience in the development and applications of UV systems and from scientific and technical works, the book's authors provide several useful examples that show the great interest of UV spectrophotometry for water and soil monitoring. At the end of the book, the UV spectra library of previous editions is updated with new chemicals of interest."
Includes bibliographical references and index.
Keywords: Optical spectroscopy; Ultraviolet spectrometry; Environmental monitoring -- Methodology; Spectrophotometry -- Technique; Water quality -- Measurement